Structure of the semigroup $OT_n$ - Pekhterev, V. O. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study the structure of the semigroup $OT_n$, which is a unique (up to an isomorphism) $R$-section of the semigroup $T_n$. For this semigroup, we describe Green relations, determine regular and nilpotent elements, describe maximal nilpotent subsemigroups, and determine the unique irreducible system of generatrices and maximal subsemigroups.